Social engineering / Raziah Bi Mohamed Sadique and Musliha Musman - Mohamed Sadique, Raziah Bi; Musman, Musliha (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
Losses suffered by Malaysian since 2017 from cyber-crime frauds has so far accumulated to RM2.23 billion (NST, 16 July 2021) up to June 2021 totalling to 67,552 cases been reported. More than 50% of the reported cases on cyber-crime frauds is e-commerce fraud and investment scams. This is only the reported amount, and sadly many more goes unreported. E-commerce and investment fraud seems to be easily committed as it is easy to manipulate information and people. How information is being shared nowadays provides opportunities for scammers and fraudsters to take advantage on the information widely available. WhatsApp, Instagram, twitter, Facebook, emails, blogs, and many more are among the mediums where information can be retrieved, stalked, collected, and used by the fraudsters. The information is used to manipulate and deceive the victims. The deception and manipulation of individuals, especially in obtaining their personal data is known as social engineering. Why is it so easy for someone to give away their personal information which include security data to others? Are they stupid? Surprisingly, in majority of cases the victims are not stupid. They are highly educated, understand the essence of fraud and cautious individuals.